2013
DOI: 10.2967/jnumed.112.114025
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Transporter Binding Does Not Correlate with Clinical Severity in Dementia with Lewy Bodies

Abstract: Patients who have dementia with Lewy bodies (DLB) show both clinical and histopathologic overlap with Alzheimer disease patients and Parkinson disease patients. In this study, we correlated the core features of DLB (dementia, parkinsonism, hallucinations, and fluctuations) with striatal dopamine transporter (DAT) availability as assessed with SPECT and 123 I-N-(3-iodoprop-2E-enyl)-2-b-carbomethoxy-3b-(4-methylphenyl) nortropane ( 123 I-PE2I) in patients with newly diagnosed DLB. Methods: Two hundred eighty-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 36 publications
1
21
2
1
Order By: Relevance
“…These discrepancies could be owing to differences in study design or applied tests. For example, Ziebell et al found no association with severity of parkinsonism or cognition using only global scales such as the H & Y and MMSE scales, and Walker et al found also no association between striatal DAT binding and total UPDRS motor score or H & Y stage in DLB, compared to early PD showing an association . In contrast, we found associations using more‐detailed motor subscores and specific neuropsychological tests.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…These discrepancies could be owing to differences in study design or applied tests. For example, Ziebell et al found no association with severity of parkinsonism or cognition using only global scales such as the H & Y and MMSE scales, and Walker et al found also no association between striatal DAT binding and total UPDRS motor score or H & Y stage in DLB, compared to early PD showing an association . In contrast, we found associations using more‐detailed motor subscores and specific neuropsychological tests.…”
Section: Discussioncontrasting
confidence: 86%
“…An inverse association was found between striatal DAT binding and visual hallucinations and between caudate nucleus DAT binding and delusions, depression, and apathy . In contrast, in another study, striatal DAT binding did not correlate with motor severity, global cognition, cognitive fluctuations, or hallucinations . These discrepancies could be owing to differences in study design or applied tests.…”
Section: Discussionmentioning
confidence: 81%
“…This is providing a useful diagnostic tool for differentiation between AD and DLB, while research is ongoing to identify the cognitive deficits associated with that deficit and potential targeted therapeutic interventions [457]. …”
Section: Contribution and Role Of Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Unlike several mGlu 1 or mGlu 5 -targeting PET radiotracers in human use, 4045 there is an unmet need for probing mGlu 2 in clinical research and drug development towards this important receptor subtype in the glutamatergic pathway. As shown in Figure 1, there are continuous research efforts in the development of mGlu 2 PET tracers, 4043 including [ 11 C]CMGDE ( 1 ), 46,47 [ 11 C]JNJ-42491293 ( 2 ), 48,49 [ 18 F]FE-JNJ42491293 ( 3 ), 50 [ 11 C]CMDC ( 4 ) 51 and two tracers ( 18 F-compound 5 and 11 C-compound 6 ) in the patent literature. 52,53 Among these studies [ 11 C]CMGDE ( 1 ), the first mGlu 2 radiotracer based on a prodrug of an antagonist LY341495, provided a foundation for the further development of a specific mGlu 2 tracer.…”
Section: Introductionmentioning
confidence: 99%